Peran Dukungan Sosial Terhadap Work Life Balance Perempuan Pekerja - Afrida Nur Chasanah (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This study aims to identify forms of social support for the work-life balance of female workers in Mataram City. Using a qualitative approach with a single instrumental case study, the research involves three female workers with various social backgrounds. The social support received, whether from family, colleagues, or the workplace, was found to be a key factor in maintaining the balance between work and personal life. The results indicate that support from the social environment, particularly emotional and instrumental support, helps female workers manage stress, improve well-being, and remain productive at work. Furthermore, differences in social status, such as marriage and child-rearing responsibilities, influence the type of support received by the respondents. This study underscores the importance of social support in maintaining life balance and suggests that companies provide flexible working hours, while families share caregiving responsibilities.